In Vitro Evaluation of Concentrate Mixtures Containing Incremental Level of Rice Dried Distillers Grain with Solubles Replacing Oil Cakes in Concentrate Mixture - Yogi, R. K.; Thakur, S. S.; Mohini, Madhu; Singh, S. K.; Malik, Tariq (Indian Journal of Animal Nutrition, 2017)
Oil cakes of concentrate mixture (% parts: maize 22, barley 16, wheat bran 15, deoiled rice bran 15, groundnut cake 25, mustard oil cake 10, mineral mixture 2 and common salt 1) in control group were replaced by rice dried diets distillers grains with solubles (RDDGS) at the levels of 25, 50, 75 and 100% on nitrogen basis. About 200 mg of each air-equilibrated samples of concentrate mixtures were evaluated by using in vitro gas production technique. Concentration of NH3-N, total volatile fatty acids and proportion of propionate at the expense of acetate and butyrate was decreased (P